1996
DOI: 10.1002/jhrc.1240190902
|View full text |Cite
|
Sign up to set email alerts
|

Relative velocity profile and flow‐rate in sedimentation field‐flow fractionation

Abstract: SummaryAlthough the classical retention theory is used for interpreting data or optimizing separations in sedimentation field-flow fractionation (SedFFF), as in most other field-flow fractionation techniques, the assumption of a parabolic flow profile on which this theory is based is not rigorously correct in SedFFF because of the curvature of the channel walls. In order to examine quantitatively the influence of this effect, the relative velocity profile in SedFFF is obtained by solving the Navier-Stokes equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…The implementation of the proposed approach is relatively simple and is summarized as follows. First, the flow distortion parameter, ν, is computed or estimated (see refs and for estimation of ν in thermal FFF and sedimentation FFF, respectively). With this value of ν and the experimentally determined retention ratio, R , λ app is computed from eq 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of the proposed approach is relatively simple and is summarized as follows. First, the flow distortion parameter, ν, is computed or estimated (see refs and for estimation of ν in thermal FFF and sedimentation FFF, respectively). With this value of ν and the experimentally determined retention ratio, R , λ app is computed from eq 3.…”
Section: Discussionmentioning
confidence: 99%
“…In sedimentation FFF, deviations from the parabolic flow profile are due to the curvature of the flow streamlines. It can be shown that the ν parameter of the approximate third-degree polynomial velocity profile is equal to plus or minus one-third of the curvature ratio, i.e., of the ratio of w to the average radius of curvature of the two channel walls, R c , the sign depending on whether the accumulation wall is the inner or outer wall . In present-day sedimentation FFF systems, the curvature ratio is very small, and the deviation of the flow profile is not significant.…”
mentioning
confidence: 99%
“…Nevertheless, when the ratio of the channel thickness to the curvature radius is as low as that of the channel used in the present study, the correction to be brought to Eq. (8) can be safely neglected [15]. Experimentally, R allows to calculate the value of the k parameter, which gives information on particle effective mass or size using Eqs.…”
Section: Theorymentioning
confidence: 99%